2020
DOI: 10.1073/pnas.2012357117
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin B 12 -dependent biosynthesis ties amplified 2-methylhopanoid production during oceanic anoxic events to nitrification

Abstract: Bacterial hopanoid lipids are ubiquitous in the geologic record and serve as biomarkers for reconstructing Earth’s climatic and biogeochemical evolution. Specifically, the abundance of 2-methylhopanoids deposited during Mesozoic ocean anoxic events (OAEs) and other intervals has been interpreted to reflect proliferation of nitrogen-fixing marine cyanobacteria. However, there currently is no conclusive evidence for 2-methylhopanoid production by extant marine cyanobacteria. As an alternative explanation, here w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 109 publications
5
15
0
Order By: Relevance
“…The high 2-MeHops' index during some of the geological events (Figure 4) could therefore (partly) be explained by an expansion of Nitrobacter that drove the high rates of nitrification. A similar hypothesis was recently proposed by Elling et al, (2020). They used cultures of Nitrobacter vulgaris AB1 and argued the high 2-MeHops' level observed during OAEs reflects an expansion of Nitrobacter in response to high rates of nitrification.…”
Section: What Drove the Elevated Sedimentary Occurrence Of 2-mehop?supporting
confidence: 74%
“…The high 2-MeHops' index during some of the geological events (Figure 4) could therefore (partly) be explained by an expansion of Nitrobacter that drove the high rates of nitrification. A similar hypothesis was recently proposed by Elling et al, (2020). They used cultures of Nitrobacter vulgaris AB1 and argued the high 2-MeHops' level observed during OAEs reflects an expansion of Nitrobacter in response to high rates of nitrification.…”
Section: What Drove the Elevated Sedimentary Occurrence Of 2-mehop?supporting
confidence: 74%
“…This idea is supported by proto-North Atlantic OAE biomarker distributions, which show a high abundance of BHP degradation products that are methylated at the C-2 position (2Me-hopanoids) . Recent experimental results have shown that these compounds are produced in abundance by nitrite oxidizing bacteria of the genus Nitrobacter (Elling et al, 2020). This scenario is also con-sistent with model predictions and data compilations for upwelling regions during OAE-2, in which all components of the nitrogen cycle are greatly amplified in response to higher simulated phosphorous inputs (Naafs et al, 2019).…”
Section: Implications For Ocean Anoxiasupporting
confidence: 75%
“…Relative abundances of major bacteriohopanepolyols (BHPs) are shown in panels a–d (BHT: bacteriohopanetetrol; BHaminotriol: 35‐aminobacteriohopanetriol; and BHaminopentol: aminobacteriohopanepentol). Abundances of total BHPs relative to 2‐methyl BHPs and the non‐functionalized hopanoids diploptene and 2‐methyl diploptene are shown in panels e–h (data for panel h from Elling et al, 2020). Abundances of total hopanoids (BHPs + 2‐methyl BHPs + diploptene + 2‐methyl diploptene) are shown in panels i–l (vertical line: average; n.a., not available).…”
Section: Resultsmentioning
confidence: 99%